Measuring seismic anisotropy in the mantle wedge of Japan's subduction system using shear wave splitting of SKS and SKKS waves - Pierce, Jamie, author; Schutt, Derek, advisor; Breidt, Jay, committee member; Egenhoff, Sven, committee member; Elkins, Joe, committee member; Harry, Dennis, committee member (Colorado State University. Libraries, 2014)
Mantle flow patterns can provide a better understanding of mantle deformation and composition in subduction systems. These flow patterns can be inferred by measuring seismic anisotropy. Previous anisotropy studies of Japan's subduction system have found complex fast axis polarizations. Here we seek to better constrain fast axis directions through shear wave splitting of SKS and SKKS waves from events with magnitudes greater than 6.5. Data were collected from the Japanese National Research Institute for Earth Science and Disaster Preventions (NIED) F-net array for stations located over all of Japan. Results from shear wave splitting measurements show trench-parallel fast axes trends near the Ryukyu and Japan Trenches and trench-perpendicular fast axes further away from these trenches. Fast axes near the Nankai Trough align with the subducted plate motion. The Kuril Trench fast axes are roughly perpendicular to subducted plate motion. A simple 2D corner flow model can explain the flow of the mantle wedge if B-type olivine deformation, indicative of hydrated asthenosphere under high stress, is the source of the fast axes perpendicular to mantle flow direction near the Ryukyu Trench, Japan Trench, and Kuril Trench.
Keywords: mantle wedge; SKS; SKKS; seismic anisotropy; shear wave splitting; Japan